Vegetation Types and their Influence on some Secondary Nutrients and Micronutrients in Soils of Meghalaya Forests - Bala Krishna Reddy, M. (Indian Forester, 2010)
The relationship between soil and vegetation is both dynamic and temporal. The variation in soil properties across the forests in Megbalayais a result of interplay of several factors, chief among which are climate, topography, tree species composition and state of health of the sylvan ecosystem. Soil pH had a direct bearmg on micronutrient content of the soils of the forests. Apart from the observation that certain important soil characteristics are well correlated with the vegetation types in the virgin forest tracts of Meghalaya it was also found that some secondary Dutrients and micronutrlents serve as useful indicators of state of health olthe forest ecosystems olthe State.